2004
DOI: 10.1029/2004gl019865
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric anomalies observed during earthquake occurrences

Abstract: [1] Appearance of anomalies in the atmosphere before earthquakes (EQs) has been verified, through observation of anomalous transmission of VHF electromagnetic (EM) waves beyond line-of-sight. Anomalous increase of the received intensity for a few minutes -several hours on a day was identified by the previous 15-day running median and its inter-quartile range. The cross-correlation between the EQ occurrences and the anomalies shows that the appearance of anomalies was significantly enhanced within 5 days before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 5 publications
2
44
0
Order By: Relevance
“…To find out the relation between the anomalous propagation and seismicity, we adopted statistical analysis to the observational results and calculated the probability gain, which is the ratio of the observational probability to the non-related probability. These are further distinguished from the previous reports (Fujiwara et al, 2004;Yonaiguchi et al, 2007).…”
Section: Introductionmentioning
confidence: 87%
“…To find out the relation between the anomalous propagation and seismicity, we adopted statistical analysis to the observational results and calculated the probability gain, which is the ratio of the observational probability to the non-related probability. These are further distinguished from the previous reports (Fujiwara et al, 2004;Yonaiguchi et al, 2007).…”
Section: Introductionmentioning
confidence: 87%
“…Fujiwara et al (2004) observed that the appearance of atmospheric anomalies associated with the anomalous transmission of VHF EM-waves beyond line-of-sight was significantly enhanced within the 5-day period immediately preceding earthquakes of moderate magnitude (generally, M ≥ 4.8).…”
Section: Ground and Space Short-term Seismic-associated Eme Signalsmentioning
confidence: 95%
“…Furthermore, Takano et al (2004) found, additionally, some anomalous reception of overseas TV broadcasting signals in Japan, which is believed to be attributed to seismo-ionospheric effect. Recently, based on the hypothesis of seismo-atmospheric perturbation as suggested by Fukumoto et al (2001), Fujiwara et al (2004) attempted to estimate the correlation between the anomalous VHF signal reception and earthquake. The crosscorrelation between the two has shown that the appearance of anomalies is significantly enhanced within 5 days before an earthquake with magnitude X4.8.…”
Section: Introductionmentioning
confidence: 99%